After The Revelation of the Name of God: Two Ways of Speaking - Malcius, Ramūnas Boleslovas (Religija ir kultūra, 2015)
[full article and abstract in Lithuanian; abstract in English] This article deals with the problem of speaking about God (Otherness). The author maintains that Revelation alone makes it possible to speak about God, but again, this speech manifests itself as a silence. The problem of talking about God is examined through the approach of philosophical theology, which also emphasizes the motive of Revelation. When God revealed His name, there was not one way to speak about God. With reference to the Revelation, philosophy gains the Christian motives that open new perspectives for speaking on God’s theme. On the basis of Thomism, speaking about God is not problematic – it is enough to highlight certain ontological differences, and it becomes clear what we should call God. However, such a speech does not avoid the aspect of speaking “about.” It is quite easy to adopt the onto-theological attitude, forgetting that the most meaningful way of talking about God rests on being silent. However, silence takes on a double meaning. On the one hand, silence is necessary for those who have not been given knowledge through Revelation and, on the other hand, silence is necessary when the secrets of the Kingdom of God are given by the very way of God’s Revelation.